Impact of Europium and Niobium Doping on Hafnium Oxide (HfO2): Comparative Analysis of Sol–Gel and Combustion Synthesis Methods - Laganovska, Katrina; Vitola, Virginija; Einbergs, Ernests; Bite, Ivita; Zolotarjovs, Aleksejs; Leimane, Madara; Tutens, Gatis; Smits, Krisjanis (MDPI, 2024)
This study compares HfO2 ceramics synthesized using sol–gel and combustion methods, emphasizing the impact of the method of synthesis on the resulting properties of the material. The research findings illustrate morphological differences between sol–gel and combustion-derived HfO2. While sol–gel samples displayed irregular nanoparticles with pronounced boundaries, combustion samples revealed more homogeneous structures with particles tending towards coalescence. It was discerned that Eu3+ doping induced oxygen vacancies, stabilizing the tetragonal phase, while subsequent doping with Nb5+ significantly reduced these vacancies, which was also observed in photoluminescence analysis. Furthermore, combustion synthesis left fewer organic residues, with urea presence during synthesis contributing to residual organic components in the material. XPS analysis was used to evaluate the presence of oxygen-deficient hafnia sub-oxide in the samples. The study underscores the important role of tailored synthesis methods in optimizing the properties and applications of HfO2. © 2023 by the authors. This is an open-access article Laganovska, K.; Vitola, V.; Einbergs, E.; Bite, I.; Zolotarjovs, A.; Leimane, M.; Tunens, G.; Smits, K. Impact of Europium and Niobium Doping on Hafnium Oxide (HfO2): Comparative Analysis of Sol–Gel and Combustion Synthesis Methods. Ceramics 2024, 7, 15-28. https://doi.org/10.3390/ceramics7010002 published under the CC BY 4.0 licence.
The financial support of the European Regional Development Fund (ERDF) Project No. 1.1.1.1/21/A/055 is greatly acknowledged. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement no. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; charge compensation; combustion; HfO2; metal oxide; oxygen vacancies; photoluminescence; sol–gel; XPS